Strategy Towards Quality Madrasah: Transforming Teachers Into Madrasah Quality Assurance Unit Architects: Strategi Menuju Madrasah Berkualitas: Mentransformasikan Guru Menjadi Arsitek Unit Penjaminan Mutu Madrasah - Moh. Harun Al Rosid; Ina Kholifatun Nikmah; Amir Karim (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2025)
The purpose of this study is to analyze the madrasah's strategy in achieving quality by transforming teachers into architects of the madrasah quality assurance unit. This research approach is qualitative with a case study design. The location of this research is Madrasah Ibtidaiyah Al Falah Sambimulyo Bangorejo Banyuwangi. The researcher is the key instrument in collecting research data. The subjects or informants in this study are the madrasah principal, teachers and committee. The data collection techniques used are participant observation, in-depth interviews, and document studies. This data analysis uses the Miles, Huberman, and Saldana analysis model, namely: data condensation, data presentation, and conclusion drawing/verification. Data validity testing uses credibility, dependability, and confirmability tests. To ensure data validity, data checking is carried out through continuous observation, triangulation, member checking, peer discussion, and checking the adequacy of references. MI Al Falah's journey towards becoming a superior madrasah is driven by three fundamental strategies: Aligning Perceptions of SPMM, Transforming Teachers as Quality Architects, and Implementing SPMM Based on Digital Evidence and a Quality Culture. The successful implementation of this internal quality assurance depends on the collective recognition that SPMM is an agent of change that drives a continuous cycle of quality improvement, not just an administrative unit. Teacher transformation through strengthening pedagogical competencies integrated with quality assurance skills, supported by distributed leadership and a Professional Learning Community (PLC) culture, has transformed quality assurance into a shared responsibility